Effect of Using e-Commerce Platforms, Influencer Marketing, Electronic Word Of Mouth on Purchasing Decisions on MSMEs Batik Products in Kediri Regency - Harwida, Gleydis; Novilia, Evita; Mahendra, Angga Martha (ProBisnis : Jurnal Manajemen, 2025)
This study analyzes the effect of e-commerce platforms, influencer marketing, and electronic word of mouth (e-WOM) on consumer purchasing decisions. The approach used is quantitative with a causal associative research type. Data were collected through questionnaires from 100 respondents who had purchased batik products online. The instrument was tested for validity and reliability, then analyzed using multiple linear regression. The results showed that the three independent variables, namely the use of e-commerce platforms, influencer marketing, and e-WOM, positively and significantly affected purchasing decisions. These findings confirm that digital marketing strategies are important in driving consumer purchasing decisions. This research provides practical contributions for batik MSME players in developing effective digital promotion strategies and theoretical contributions in studying consumer behavior in the digital era.